Hey from my notes in my PS book it seems I have solved this some time in the past, but I cannot seem to get the indices straight this time around. So in deriving the Feynman photon-propagator which includes a general parameter $\xi$ (see PS equation 9.58 page 297) PA find the solution of the following equation

$${\large[}-k^2g_{\mu\nu}+\underbrace{(1-\xi^{-1})}_{-\chi}k_\mu k_\nu{\large]}\tilde{D}_F^{\nu\rho} = \mathrm{i}\delta_\mu^{\rho}\tag{9.57b}$$

I try to rewrite this as $$ {\large[}g_{\mu\nu}+\chi \frac{k_\mu k_\nu}{k^2}{\large]}\tilde{D}_F^{\nu\rho} = \frac{-\mathrm{i}}{k^2+\mathrm{i}0}\delta_\mu^{\rho}$$

and then try to find the inverse of

$${\large[}g_{\mu\nu}+\chi \frac{k_\mu k_\nu}{k^2}{\large]}$$

by using the identity for matrices

$$\tag{$\star$}(A+B)^{-1} = A^{-1} - \frac{1}{1+g}A^{-1}BA^{-1}$$

where $g= \mathrm{tr}(BA^{-1})$ (see this MSE answer).

As suggested in this related Phys.SE post, one can simply write the most general expression (respecting the symmetries of the theory) for $\tilde{D}_F^{\mu\nu} = Ag^{\mu\nu}+B k^\mu k^\nu$, plug into equation $(9.57\mathrm{b})$ and find the functions $A$ and $B$.

But the question remains whether one can use a theorem from linear algebra such as $(\star)$ above? What trace should one use in that case, etc?

The answer is btw the familiar Feynman photon propagator

$$\tilde{D}_F^{\mu\nu}(k) = \frac{-\mathrm{i}}{k^2+\mathrm{i}0} {\large[}g^{\mu\nu}-(1-\xi) \frac{k^\mu k^\nu}{k^2}{\large]}.\tag{9.58}$$


Clearly from your question above, we identify $$ A_{\mu \nu} = g_{\mu \nu}, B_{\mu \nu} = \chi \frac{k_\mu k_\nu}{k^2} $$

Since the Minkowski metric is its own inverse, we know that $$(A_{\mu \nu})^{-1} = A^{\mu \nu} = g^{\mu \nu}$$

We then find that $$g = \mathrm{tr}(B A^{-1}) = \mathrm{tr}(B_{\mu\nu} A^{\nu \rho} ) = B_{\mu\nu} A^{\nu \mu} = \chi \frac{k_\mu k_\nu g^{\nu \mu}}{k^2} = \chi $$

And $$ (A_{\mu \nu} + B_{\mu \nu})^{-1} = A^{\mu \nu} - \frac{1}{1+g} A^{\mu \rho} B_{\rho \sigma} A^{\sigma \nu} $$

Here I have introduced new indices $\rho$ and $\sigma$ to make sure the matrix multiplications are carried out the right way. Plugging everything in, we find $$ \left(g_{\mu \nu} + \chi \frac{k_\mu k_\nu}{k^2} \right)^{-1} = g^{\mu \nu} - \frac{\chi}{1+\chi} \frac{k^\mu k^\nu}{k^2} $$

Rewriting this into the form of (9.58) is left as an exercise for the reader ;).


While a correct answer has been provided, based on Ken Miller's theorem on the inversion of sums of matrices, it can also be solved by the more specific, Sherman-Morrison formula.

It asserts under certain conditions that,

$$(A_{\mu\nu} + U_\mu V_\nu)^{-1} = A^{\mu\nu} - \frac{A^{\mu\lambda}U_\lambda U_\sigma A^{\sigma \nu}}{1 + V_\mu A^{\mu\nu}U_\nu}.$$

To simplify matters, we redefine,

$$\tilde{k}^\mu := \frac{\sqrt{\chi}}{|k|}k^\mu$$

so that we must find,

$$(\eta_{\mu\nu} + \tilde k_\mu \tilde k_\nu)^{-1} = \eta^{\mu\nu} - \frac{\tilde k^\mu \tilde k^\nu}{1+\tilde k \cdot \tilde k} = \eta^{\mu\nu} - \frac{\chi}{1+\chi} \frac{k^\mu k^\nu}{k^2}$$

and noting that,

$$\frac{\chi}{1+\chi} \bigg\vert_{\chi = \frac{1}{\xi}-1} = 1 - \xi$$

we recover the desired result,

$$\eta^{\mu\nu} + (\xi-1) \frac{k^\mu k^\nu}{k^2}.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.